The INSIG2 rs7566605 genetic variant does not play a major role in obesity in a sample of 24,722 individuals from four cohorts - Mosley Thomas H; Dent Robert; McPherson Ruth; Lewis Cora E; Kao Wen; Hanis Craig L; Fornage Myriam; Bressler Jan; Pennacchio Len A; Boerwinkle Eric (BMC, 2009)
Abstract Background In a genome-wide association study performed in the Framingham Offspring Cohort, individuals homozygous for the rs7566605 C allele located upstream of insulin-induced gene 2 (INSIG2) were reported to incur an increased risk of obesity. This finding was later replicated in four out of five populations examined. The goal of the study reported here was to assess the role of the INSIG2 single nucleotide polymorphism (SNP) in susceptibility to obesity in the prospective longitudinal Atherosclerosis Risk in Communities (ARIC) study (n = 14,566) and in three other cohorts: the Coronary Artery Risk Development in Young Adults (CARDIA) study (n = 3,888), the Genetic Epidemiology Network of Arteriopathy (GENOA) study (n = 4,766), and extremely obese and lean individuals ascertained at the University of Ottawa (n = 1,502). The combined study sample is comprised of 24,722 white, African-American, and Mexican-American participants. Methods Differences in mean body mass index (BMI) and other anthropometric measures including weight, waist circumference, and waist-to-hip ratio were assessed by a general linear model in individuals categorized by INSIG2 rs7566605 genotype. Multivariable logistic regression was used to predict the risk of obesity (BMI ≥ 30 kg/m2). Results There was no discernable variation in the frequencies of the three INSIG2 SNP genotypes observed between white, Hispanic, and African-American obese individuals and non-obese study subjects. When the relationship between rs7566605 and BMI considered either as a categorical variable or a continuous variable was examined, no significant association with obesity was found for participants in any of the four study populations or in a combined analysis (p = 0.38) under a recessive genetic model. There was also no association between the INSIG2 polymorphism and the obesity-related quantitative traits except for a reduced waist-to-hip ratio in white ARIC study participants homozygous for the C allele, and an increased waist-to-hip ratio in African-Americans in the ARIC cohort with the same genotype (p = 0.04 and p = 0.01, respectively). An association with waist-to-hip ratio was not seen when the combined study sample was analyzed (p = 0.74). Conclusion These results suggest that the INSIG2 rs7566605 variant does not play a major role in determining obesity risk in a racially and ethnically diverse sample of 24,722 individuals from four cohorts.